Pengaruh Agrevitas Pajak dan Media Exposure terhadap Pengungkapan Corporate Social Responsibility dengan Profitabilitas sebagai Variabel Moderasi - Ayunita Ajengtiyas Saputri Mashuri; Husnah Nur Laela Ermaya (Jurnal Ekonomi, 2020)
Abstract - Social and Environmental Responsibility must be owned by the company in generating profits. CSR disclosure has several factors, including the factors of tax aggressiveness, media exposure and profitability. This research is a quantitative study that aims to determine the effect of Tax Aggressiveness, Media Exposure on Disclosure of Corporate Social Responsibility (CSR) with moderated profitability. The population used in this study are industrial companies in the consumer goods sector which were listed on the Indonesia Stock Exchange (IDX) in the 2014-2018 period. By using purposive sampling method, 80 companies were obtained as research samples. The analytical method used in this study is multiple linear regression. In this study also includes the classical assumption test that is normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The results of this study indicate that (1) Tax Aggressiveness has a significant effect on CSR Disclosures (2) Media Exposure has a significant effect on CSR disclosure and (3) profitability is able to strengthen and weaken tax aggressiveness and media exposure in influencing Corporate Social Responsibility disclosure.